2006
DOI: 10.1021/jp056990y
|View full text |Cite
|
Sign up to set email alerts
|

Size Dependence of Protein Diffusion Very Close to Membrane Surfaces:  Measurement by Total Internal Reflection with Fluorescence Correlation Spectroscopy

Abstract: The diffusion coefficients of nine fluorescently labeled antibodies, antibody fragments, and antibody complexes have been measured in solution very close to supported planar membranes by using total internal reflection with fluorescence correlation spectroscopy (TIR-FCS). The hydrodynamic radii (3-24 nm) of the nine antibody types were determined by comparing literature values with bulk diffusion coefficients measured by spot FCS. The diffusion coefficients very near membranes decreased significantly with mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 62 publications
5
36
0
Order By: Relevance
“…With HI, the total velocity profile in the interior decreases toward the wall. This slowdown in diffusion due to HI is expected from both theoretical and experimental studies (7). By separately measuring the tangential (red) and radial (orange) components of velocity, we also observe that the slowdown toward the wall is entirely in the radial component.…”
Section: Decrease In Diffusion Toward the Cell Wall Due To Hydrodynamicsupporting
confidence: 72%
See 1 more Smart Citation
“…With HI, the total velocity profile in the interior decreases toward the wall. This slowdown in diffusion due to HI is expected from both theoretical and experimental studies (7). By separately measuring the tangential (red) and radial (orange) components of velocity, we also observe that the slowdown toward the wall is entirely in the radial component.…”
Section: Decrease In Diffusion Toward the Cell Wall Due To Hydrodynamicsupporting
confidence: 72%
“…Previous theoretical and experimental studies have shown that diffusion slows down near planar membranes and that this is due to HI (7). Most studies of diffusion in confined spaces have addressed simple geometries such as parallel walls, in part for their simplicity and in part for their application to microfluidic devices (8)(9)(10).…”
mentioning
confidence: 99%
“…For this kind of application, potential hydrodynamic surface effects should be kept in mind. The diffusion coefficients of large biomolecules very close to supported planar membranes decrease more strongly than expected from literature values for freely diffusing particles (Pero et al, 2006). Nevertheless, TIR-FCS, as TIRFM, is restricted to surface measurements with a maximum illumination depth in the range of 200 nm.…”
Section: Resolution Enhancements and Fcsmentioning
confidence: 76%
“…Processes commonly studied with FCS include diffusion, flow, binding, rotation, photo-physics, bleaching and conformational changes [17][18][19]. In combination with total internal reflection excitation, so-called TIR-FCS, the technique has been used to quantify dynamic events at interfaces like reversible adsorption/desorption kinetics of dye molecules [20,21] and monodisperse polymers [22] to solid surfaces, dye transport in sol-gel films [23], ligand-receptor kinetics [24], antibody diffusion near phospholipid bilayers [25,26] and lateral mobility of proteins in cellular membranes [27]. However, there are to our knowledge no reported TIR-FCS studies of surface kinetics of protein-surfactant interactions.…”
Section: Introductionmentioning
confidence: 99%